2021
DOI: 10.1007/s11676-021-01338-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological plasticity response to low nitrogen stress in black cottonwood (Populus deltoides Marsh.)

Abstract: It is important to evaluate nitrogen use efficiency and nitrogen tolerance of trees in order to improve their productivity. In this study, both were evaluated for 338 Populus deltoides genotypes from six provenances. The plants were cultured under normal nitrogen (750 μM NH4NO3) and low nitrogen (5 μM NH4NO3) conditions for 3 months. Growth, chlorophyll content and glutamine synthetase activity of each genotype were measured. Under low nitrogen, heights, ground diameter, leaf area, leaf and root biomass, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…It seems that the growth of sugar beet under N stress was connected to the duration and concentration of N treatments. This result is similar to the results of Chen et al [38], where with reduced N, the root system of black cottonwood adjusted in response to stress reaction, leading to enhanced transfer of substances from the fallen leaves to the roots. However, with extended periods of stress, the substances produced by the leaves was not sufficient for root development; therefore, decelerating the root development.…”
Section: Plos Onesupporting
confidence: 92%
“…It seems that the growth of sugar beet under N stress was connected to the duration and concentration of N treatments. This result is similar to the results of Chen et al [38], where with reduced N, the root system of black cottonwood adjusted in response to stress reaction, leading to enhanced transfer of substances from the fallen leaves to the roots. However, with extended periods of stress, the substances produced by the leaves was not sufficient for root development; therefore, decelerating the root development.…”
Section: Plos Onesupporting
confidence: 92%
“…Moso bombo is one of the woody plants that improved its morphological and physiological response to stress conditions under ammonium ion (NH 4 ) [25]. Chen et al [26] reported that Populus deltoides significantly promoted root growth that uptakes more N from the soil to improve nitrogen use efficiency under low-N conditions. Invasive plant species also have the capability to live in stressful conditions without any damaging effects because they have strong ecological adaptability [27].…”
Section: Introductionmentioning
confidence: 99%
“…At present, such situations as the low nitrogen content in most cultivated land, various abiotic stress and low nitrogen use e ciency (NUE) of crops, directly or indirectly lead to the occurrence of nitrogen stress. Accordingly, in order to ensure the normal growth of crops under nitrogen stress, plants have evolved a series of cellular, physiological and molecular mechanisms to adapt to the stress response, such as improving the biosynthesis to alleviate the nitrogen stress response, increasing the content of plant hormones and the expression of stress genes (Imamura et al, 2009;Babst et al, 2019;Chen et al, 2021a;Jin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%